2016
DOI: 10.1002/ana.24805
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive working memory training improved brain function in human immunodeficiency virus–seropositive patients

Abstract: ObjectiveWe aimed to evaluate the effectiveness of an adaptive working memory (WM) training (WMT) program, the corresponding neural correlates, and LMX1A‐rs4657412 polymorphism on the adaptive WMT, in human immunodeficiency virus (HIV) participants compared to seronegative (SN) controls.MethodsA total of 201 of 206 qualified participants completed baseline assessments before randomization to 25 sessions of adaptive WMT or nonadaptive WMT. A total of 74 of 76 (34 HIV, 42 SN) completed adaptive WMT and all 40 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 51 publications
0
49
0
1
Order By: Relevance
“…Importantly, the decreases observed after training persisted with no change after five weeks without training. Previous research found stability effects on the trained task (n-back; 29,40 ), but this is the first time the stability of neural transfer effects has been demonstrated.…”
Section: Discussionmentioning
confidence: 64%
“…Importantly, the decreases observed after training persisted with no change after five weeks without training. Previous research found stability effects on the trained task (n-back; 29,40 ), but this is the first time the stability of neural transfer effects has been demonstrated.…”
Section: Discussionmentioning
confidence: 64%
“…The association of allelic frequencies of the LMX1A and neurological diseases has been studied only to a limited extent ( Bergman et al, 2010 ; Rolstad et al, 2015 ). For instance, LMX1A -AA carriers with HIV-associated neurocognitive disorders showed greater WM training gain than non-carriers ( Chang et al, 2017 ), whereas conflicting results exist in cognitively normal individuals ( Bellander et al, 2011 , 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…A total 106 participants were screened and were randomly but consecutively chosen from 206 participants who were being enrolled in a larger neuroimaging study of brain changes after cognitive training (Chang et al, 2016; Chang et al, 2017). However, 66 (31 HIV+ and 35 SN) of these participants agreed to be co-enrolled in the current study to evaluate the neuroimaging signature of pain (between June 20 th 2013 to December 15 th , 2015.)…”
Section: Methodsmentioning
confidence: 99%